(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the issues of racial equality and the development of black people rights within the framework of international law. Historically, black people have suffered serious discrimination as a result of the transatlantic slave trade, colonialism, segregation and apartheid policies. Therefore, ensuring their rights has become an important task for the international community. The article also examines the role of international law and the activity of civil society in the development of black people rights. In conclusion, it is emphasized that the principle of racial equality should be recognized as one of the common legal and moral values ​​not only of black people, but also of all humanity.